2021
DOI: 10.1155/2021/5584423
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Empathy among Dental Students and Interns: A Cross-Sectional Study from Dammam, Saudi Arabia

Abstract: Objective. To evaluate empathy and its related factors among undergraduate dental students and interns enrolled in a public dental college in Dammam, Saudi Arabia. Materials and Methods. This cross-sectional study used the Jefferson Scale of Empathy-Health Profession Students (JSE-HPS) version to determine empathy in 362 dental students and interns in Dammam, Saudi Arabia. The JSE-HPS is a 20-item 7-point Likert scale questionnaire, and its score ranges from 20 to 140 with high values indicating increased empa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
4
10
0
1
Order By: Relevance
“…Mientras que en otros estudios realizados en estudiantes de Arabia Saudita las mujeres demostraron una nivel medio de empatía significativamente más alta puntuación que los varones (19,20) .…”
Section: Discussionunclassified
“…Mientras que en otros estudios realizados en estudiantes de Arabia Saudita las mujeres demostraron una nivel medio de empatía significativamente más alta puntuación que los varones (19,20) .…”
Section: Discussionunclassified
“…28 The results of the JSPE questionnaire showed high general empathy levels which is consistent with the scores collected using the same questionnaire for the same targeted population in other similar studies. 12,20,22,[28][29][30] Therefore, we failed to reject the null hypothesis that graduate students have higher empathetic tendencies due to their exposure to everyday workload stress. However, high empathy levels of dental interns and postgraduate students might be attributed to the fact that they have more experience and less exams-associated stress, and subsequently experienced more empathy than their undergraduate counterparts as reported in a previous study.…”
Section: Discussionmentioning
confidence: 99%
“…23,38 Other investigators showed either no difference in empathy levels of postgraduates during their clinical training 39,40 or even lower empathy scores in postgraduate students. 18 Several researchers stated that interns had the highest empathy levels in comparison to undergrads, 22,37,[41][42][43] while others showed lower empathy levels in dental interns. 8,17 Changes in dental students 'empathy levels could be associated initially with cultural differences, heritage, faith, passion, affective features, and social behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations